(untitled) (Sains Humanika, 2014)
The aim of this study is to investigate the correlation between organizational career program and job satisfaction using self-reported questionnaires accumulated from employees at a defence based higher learning institution in Malaysia. The results of multiple regression analysis confirmed that career management negatively and insignificantly correlated with job satisfaction while career development positively and significantly correlated with job satisfaction. This finding explains that career development is an essential predictor of job satisfaction, but career management is not an essential predictor of job satisfaction in the studied organization.Â Â